Psychometric properties of the Indonesian version of the Depression Anxiety Stress Scale: Factor structure, reliability, gender, and age measurement invariance - Darmawan Muttaqin; Serena Ripa (Psikohumaniora: Jurnal Penelitian Psikologi, 2021)
Measurement instruments that have satisfactory psychometric properties are needed to improve mental health research and services, especially in the effort to measure, identify, and monitor the psychological problems experienced by individuals. The purpose of this study is to examine the psychometric properties of the Indonesian version of the Depression Anxiety Stress Scale (DASS). The study involved 1,922 participants from Surabaya aged between 16 and 26. The data were obtained using the convenience sampling method. Testing of the factor structure, reliability, and measurement invariance of the Indonesian DASS was performed using a confirmatory factor, composite reliability, and multi-group analysis. It was found that a bifactor model consisting of specific (depression, anxiety, and stress) and general (psychological distress) factors was the best structure for the DASS. Furthermore, the model also showed satisfactory composite reliability and measurement invariance across genders. The results indicated that the Indonesian version of the DASS was a valid and reliable instrument for measuring and comparing depression, anxiety, stress, and psychological distress between genders in the Indonesian sample.